ANALISIS PERAN HUKUM ADMINISTRASI NEGARA TERHADAP UPAYA PENCEGAHAN PRAKTIK KORUPSI DALAM PEMERINTAHAN - Mutiara Gita Cahyani; Rahmania Ramadhani (Pusat Riset dan Inovasi Nasional, 2023)
Corruption is an act of misappropriation or abuse that can harm the state for personal gain. Corruption is the enemy of society because it is carried out by people who are irresponsible and this robs people of their rights. This research discusses how the government authority over corrupt practices in state administrative law and the role of state administrative law in efforts to prevent corrupt practices in government. The type of this research is normative jurdicial research with a descriptive approach. The secondary data sources in this research are observations in books, articles, journals, and other documents. Validation of this data using source triangulation techniques, and analyzed with inductive qualitative techniques. This research concludes that government authority is closely related to state administrative law because this law plays an important role in realizing good and clean governance, especially from corruption. The government can create an authority by implementing a closed system policy. To prevent the entry of outsiders and help strengthen government regulation. The role of state administrative law in corruption practices can be in the form of optimizing leadership, improving administration, increasing the integrity and synergy of the bureaucracy, as well as strengthening legal awareness regarding corruption in the community.